International Union of Basic and Clinical Pharmacology. LXXXV: calcium-activated chloride channels - Huang, Fen; Wong, Xiuming; Jan, Lily Y (Pharmacological reviews, 2012)
Calcium-activated chloride channels (CaCCs) are widely expressed in various tissues and implicated in physiological processes such as sensory transduction, epithelial secretion, and smooth muscle contraction. Transmembrane proteins with unknown function 16 (TMEM16A) has recently been identified as a major component of CaCCs. Detailed molecular analysis of TMEM16A will be needed to understand its structure-function relationships. The role this channel plays in physiological systems remains to be established and is currently a subject of intense investigation.